Detection of germline mosaicism in fathers of children with intellectual disability syndromes caused by de novo variants. Issue 4 (4th February 2022) - Frisk, Sofia; Wachtmeister, Alexandra; Laurell, Tobias; Lindstrand, Anna; Jäntti, Nina; Malmgren, Helena; Lagerstedt‐Robinson, Kristina; Tesi, Bianca; Taylan, Fulya; Nordgren, Ann
Abstract: Background: De novo variants are a common cause to rare intellectual disability syndromes, associated with low recurrence risk. However, when such variants occur pre‐zygotically in parental germ cells, the recurrence risk might be higher. Still, the recurrence risk estimates are mainly based on empirical data and the prevalence of germline mosaicism is often unknown. Methods: To establish the prevalence of mosaicism in parents of children with intellectual disability syndromes caused by de novo variants, we performed droplet digital PCR on DNA extracted from blood (43 trios), and sperm (31 fathers). Results: We detected low‐level mosaicism in sperm‐derived DNA but not in blood in the father of a child with Kleefstra syndrome caused by an EHMT1 variant. Additionally, we found a higher level of paternal mosaicism in sperm compared to blood in the father of a child with Gillespie syndrome caused by an ITPR1 variant. Conclusion: By employing droplet digital PCR, we detected paternal germline mosaicism in two intellectual disability syndromes. In both cases, the mosaicism level was higher in sperm than blood, indicating that analysis of blood alone may underestimate germline mosaicism. Therefore, sperm analysis can be clinically useful to establish the recurrence risk for parents and improve genetic counselling. Abstract : By employing droplet digital PCR, we detected paternal germline mosaicism in two intellectual disability syndromes. In both cases, the mosaicism level was higher in sperm than blood, indicating that analysis of blood alone may underestimate germline mosaicism. Therefore, sperm analysis can be clinically useful to establish the recurrence risk for parents and improve genetic counselling.